HermÄ“s Dolios: Performances of Hermes as trickster in the Homeric Hymn to Hermes - Nel, Aiden Pieter (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
This thesis explores the Greek god Hermes' representation in the Homeric Hymn to Hermes to establish the extent to which he partakes in Hynes' defined set of characteristics associated with mythological 'trickster' figures. Hermes is an unorthodox figure as although he embodies many aspects of the trickster, he willingly relinquishes some of these aspects within his hymn. I first outline and explore the trickster phenomenon and the complex methodological issue concerning global comparison. Hynes' criteria are first applied to three other tricksters the Amerindian (Winnebago) trickster Wakdjunkaga, the central African (Azande) trickster Ture and the northern European (Norse) trickster Loki, which establishes a baseline that will help determine how Hermes conforms to this typology. All three figures' cultural contexts are first addressed, as the cultural context is key in understanding a figure's potential inclusion in the trickster category. I then explore Hermes' performances within his hymn and other genres to formulate how his patron powers and actions relate to his designation as a trickster. I argue, in conclusion, that Hynes' typology is a useful tool in determining any figure's degree of 'tricksterness' and show that Hermes and the other three figures do embody Hynes' characteristics. Each, however, embodies them differently and in a specific manner. I argue that the manner in which they relate to the criteria is dictated by their respective cultural contexts, and what their narrators intended to illustrate through the stories wherein tricksters reside. I further argue that narrative intent, genre and cultural context appear to be the main factors that mould each respective figure.
Keywords: Hermes (Greek deity); Hymn to Hermes; Tricksters in literature; Loki (Norse deity); Hynes, William J; Doty, William G, 1939-; Wakdjunkaga (Winnebago Trickster); Ture (Zande Trickster)